Social Audit of MGNREGA: A Path of Community Participation in Tribal Area of Himachal Pradesh - Ram, Bhumi; Sharma, Sapna K. (International Journal of Economic, Finance and Business Statistics, 2023)
Social audit is a powerful tool for social change, community engagement, and government accountability. The technique of closely examining and assessing a program with community involvement while comparing government data with real-world experiences is known as social auditing. After the implementation of the social audit, the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) implementing agency has become increasingly transparent and accountable in its functioning. The present research paper is an attempt to know the effectiveness of social audit mechanisms in enhancing transparency, ensuring accountability, and promoting community participation in the implementation of MGNREGA in the tribal development block Bharmaur in the Chamba district of Himachal Pradesh. The paper aims to provide a comprehensive analysis of social change, people participation, and transparency through social audit practices on the execution of MGNREGA work.